METHODS OF ORGANIZING A LABORATORY AREA FOR CHILDREN OF PRESCHOOL GROUPS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Archive of Conferences, 2022)
In order to further improve the quality of education, to develop children's interest in specific sciences, to conduct interesting safe laboratory activities for children of large and pre-school groups on the basis of the state program "First Step" and to establish a special laboratory area for these experiments. the theory used is illuminated